Neuroliberalism: Cognition, context, and the geographical bounding of rationality. (August 2019) - Whitehead, Mark; Jones, Rhys; Lilley, Rachel; Howell, Rachel; Pykett, Jessica
Focusing on the rise of the behavioural sciences within the design and implementation of public policy, this paper introduces the concept of neuroliberalism and suggests that it could offer a creative context within which to interpret related governmental developments. Understanding neuroliberalism as a system of government that targets the more-than-rational aspects of human behaviour, this paper considers the particular contribution that geographical theories of context and spatial representation can make to a critical analysis of this evolving governmental project